Fluid mechanics and thermodynamics of turbomachinery - Dixon, S. L. (Sydney Lawrence) (Butterworth-Heinemann/Elsevier, 2010)
"Turbomachinery is a challenging and diverse field, with applications for professionals and students in many subsets of the mechanical engineering discipline, including fluid mechanics, combustion and heat transfer, dynamics and vibrations, as well as structural mechanics and materials engineering. Originally published more than 40 years ago, Fluid Mechanics and Thermodynamics of Turbomachinery is the leading turbomachinery textbook." "Used as a core text in senior undergraduate and graduate level courses, this book will also appeal to professional engineers in the aerospace, global power, oil and gas, and other industries that are involved in the design and operation of turbomachines. For this new edition, author S. Larry Dixon is joined by Cesare Hall from the University of Cambridge, whose diverse background of teaching, research, and work experience in the area of turbomachines is well-suited to the task of reorganizing and updating this classic text."--Jacket.